Sex-Based Morphological Affecting Post-Detachment Survival of Argulus ja-ponicus from Common Carp (Cyprinus carpio) - Gilang Septian Gilang; Kismiyati; Marina Hasan (Airlangga University, 2026)
This study looks at how differences in body shape and behavior between male and female Argulus japonicus influence their survival after separating from their host. A total of 200 specimens (100 males and 100 females) were collected from infected goldfish (Cyprinus carpio) in Sidoarjo, East Java. Each parasite was then observed individually in aerated petri dishes at a consistent room temperature of 28 °C. Microscopic observations showed that males tend to have a more elongated and slender body, while females are generally shorter and rounder. This difference is likely related to reproductive needs, especially egg production in females. The results also indicate a clear difference in survival between the sexes. Females frequently detach from the host to lay eggs, a process that appears to cause stress and may reduce their lifespan. On the other hand, males are more likely to remain attached to the host, which may help them maintain a more stable condition and live longer. Overall, these findings suggest that reproductive behavior plays an important role in determining how long these parasites can survive outside their host. This information could be useful for developing more effective control strategies in aquaculture